Performance evaluation of IEEE 802.15.4 wireless multi-hop networks: simulation and testbed approach. (14th January 2008) - Woon, Wilson T.H.; Wan, Tat-Chee
IEEE 802.15.4 for Low-Rate Wireless Personal Area Networks (LR-WPANs) standard was designed specifically for simple, low-rate, and low power applications in Wireless Sensor Networks (WSNs). It is available in ns2 simulator and numerous commercial sensor motes. In this paper a comprehensive performance evaluation of IEEE 802.15.4 using ns2 and testbed experiments is presented. The purpose is to measure the performance of the standard in various settings and compare the results obtained from simulation and realistic experiments. The performance metrics include Throughput, Packet Delivery Ratio, and Delay.